Presentation = Speech + Slides - Derik Badman (In the Library with the Lead Pipe, 2008)
Back in October, Aaron Schmidt posted “HOWTO give a good presentation” to his blog walking paper. His second bullet point of “thoughts” on good presentations is: Please don’t fill your slides with words. Find some relevant and pretty pictures to support what you’re saying. You can use the pictures to remind yourself what you’re going [...]